Cesium hydrazinidoborane, the last of the alkali hydrazinidoboranes, studied as potential hydrogen storage material. (24th June 2020) - Castilla-Martinez, Carlos A.; Granier, Dominique; Charmette, Christophe; Cartier, Jim; Yot, Pascal G.; Demirci, Umit B.
Abstract: Alkali hydrazinidoboranes MN2 H3 BH3 (M = Li, Na, K, Rb) have been developed for hydrogen storage. To complete the family of MN2 H3 BH3, we focused on cesium hydrazinidoborane CsN2 H3 BH3 (CsHB). It has been synthesized by reaction of cesium with hydrazine borane (N2 H4 BH3 ) at −20 °C under inert atmosphere, and it has been characterized. A crystalline solid (monoclinic, s.g. P 21 (No. 4)) has been obtained. Its potential for hydrogen storage has been studied by combining different techniques. It was found that, under heating at constant heating rate (5 °C min −1 ) or at constant temperature (e.g. 120 °C), CsHB decomposes rather than it dehydrogenates. It releases several unwanted gaseous products (e.g. NH3, B2 H6 ) together with H2, and transforms into a residue that poses safety issues because of shock-sensitivity and reactivity towards O2 /H2 O. Though the destabilization brought by Cs + onto the anion [N2 H3 BH3 ] − has been confirmed, the effect is not efficient enough to avoid the aforementioned drawbacks. All of our results are presented herein and discussed within the context of solid-state hydrogen storage. Graphical abstract: Image 1 Highlights: The last of the alkali hydrazinidoboranes, the cesium one, has been synthesized. Cesium hydrazinidoborane CsN2 H3 BH3 is crystalline (monoclinic, s.g. P 21 (No. 4)). Under heating, it releases several gaseous by-products together with hydrogen. The cation Cs + destabilizes the anion [N2 H3 BH3 ] − but it cannot hinder decomposition. Further works are required to make CsN2 H3 BH3 a suitable hydrogen storage material.